Characterization of a novel cytotoxic cell-penetrating peptide derived from p14ARF protein. - Johansson, H; El-Andaloussi, S; Holm, T; Mäe, M; Jänes, J; Maimets, T; Langel, U (2008)
The tumor suppressor p14ARF is widely deregulated in many types of cancers and is believed to function as a failsafe mechanism, inhibiting proliferation and inducing apoptosis as cellular response to a high oncogene load. We have found that a 22-amino-acid-long peptide derived from the N-terminal part of p14ARF, denoted ARF(1-22), which has previously been shown to mimic the function of p14ARF, has cell-penetrating properties. This peptide is internalized to the same extent as the cell-penetrating peptide (CPP) TP10 and dose-dependently decreases proliferation in MCF-7 and MDA MB 231 cells. Uptake of the ARF(1-22) peptide is associated with low membrane disturbance, measured by deoxyglucose and lactate dehydrogenase (LDH) leakage, as compared to its scrambled peptide. Also, flow cytometric analysis of annexin V/propidium iodide (PI) binding and Hoechst staining of nuclei suggest that ARF(1-22) induces apoptosis, whereas scrambled or inverted peptide sequences have no effect. The ARF(1-22) peptide mainly translocates cells through endocytosis, and is found intact inside cells for at least 3 hours. To our knowledge, this is the first time a CPP having pro-apoptopic activity has been designed from a protein.